Analisis Budaya Damai Suku To Balo dan Masyarakat Desa Bulo Bulo Kabupaten Barru Provinsi Sulawesi Selatan - Charizatul Janna Asdi Putri; Bambang Wahyudi; Anang Puji Utama; Pujo Widodo; Herlina Juni Risma Saragih (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Abstract This study aims to investigate the culture of peace between the Tobalo ethnic group and the community of Bulobulo village in South Sulawesi Province, Indonesia. Employing a qualitative approach, data were gathered through interviews, observations, and literature review. The research findings indicate that despite the Tobalo people's distinctive cultural markers, such as their prominent facial tattoos, they have deeply integrated with the surrounding community. A culture of peace is fostered through mutual respect for ethnic and cultural diversity, non-violent conflict resolution, tolerance for differences, and participation in democratic processes. The integration between the Tobalo ethnic group and the Bulobulo village community not only promotes social harmony but also strengthens the foundation for peaceful and prosperous coexistence. This underscores the importance of understanding and promoting a culture of peace as a basis for harmony among diverse communities. Keywords: Peace Culture, Desa Bulo Bulo, Tobalo Ethnic, Cultural Integration, Social Harmony Abstrak Penelitian ini bertujuan menginvestigasi budaya damai antara Suku To Balo dan masyarakat Desa Bulo Bulo di Provinsi Sulawesi Selatan, Indonesia. Melalui pendekatan kualitatif, data dikumpulkan melalui wawancara, observasi, dan telaah literatur. Hasil penelitian menunjukkan bahwa meskipun Suku To Balo memiliki ciri fisik yang unik, yaitu pola kulit yang mencolok, mereka telah mengalami integrasi yang mendalam dengan masyarakat sekitar. Budaya damai tercipta melalui penghargaan terhadap keragaman suku dan budaya, penyelesaian konflik tanpa kekerasan, toleransi terhadap perbedaan, dan partisipasi dalam demokrasi. Integrasi yang terjalin antara Suku To Balo dan masyarakat Desa Bulo Bulo tidak hanya menciptakan harmoni sosial, tetapi juga memperkuat fondasi bagi kehidupan bersama yang damai dan sejahtera. Ini menegaskan pentingnya memahami dan mempromosikan budaya damai sebagai landasan untuk harmoni antar masyarakat yang beragam. Kata Kunci: Budaya Damai, Desa Bulo Bulo, Harmoni Sosial, Integrasi Budaya, Suku To Balo